2015
DOI: 10.3109/14756366.2015.1043297
|View full text |Cite
|
Sign up to set email alerts
|

In vitro inhibition effect of some coumarin compounds on purified human serum paraoxonase 1 (PON1)

Abstract: Human serum paraoxonase 1 (PON1; EC 3.1.8.1) is a high-density lipoprotein associated, calcium-dependent enzyme that hydrolyses aromatic esters, organophosphates and lactones and can protect the low-density lipoprotein against oxidation. In this study, in vitro effect of some hydroxy and dihydroxy ionic coumarin derivatives (1-20) on purified PON1 activity was investigated. Among these compounds, derivatives 11-20 are water soluble. In investigated compounds, compounds 6 and 13 were found the most active (IC 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
0
9
0
1
Order By: Relevance
“…However, there are very few studies investigating the interaction between PON activity and pharmaceutical products …”
Section: Resultsmentioning
confidence: 99%
“…However, there are very few studies investigating the interaction between PON activity and pharmaceutical products …”
Section: Resultsmentioning
confidence: 99%
“…Several studies reported the effects of some drugs on PON1 (Arslan et al, 2012; Gokce et al, 2016; Kiranoglu et al, 2007; Sinan et al, 2006). In the literature, there are few studies investigating the interactions between pharmaceutical products and PON1 activity.…”
Section: Discussionmentioning
confidence: 99%
“…These enzymes have been purified from different sources. Drug interaction studies of these essential enzymes have made significant contributions to the academic literature in the field of drug metabolism (Arslan et al, 2012; Gokce et al, 2016; Karatas, Uslu, Alıcı, Gokce, Gencer, & Arslan, 2016; Karatas Uslu, Alıcı, Gokce, Gencer, Arslan, Arslan, et al, 2016; Kiranoglu et al, 2007; Sinan et al, 2006). However, there are not enough studies about the impact of cardiac drugs on PON1 activity.…”
Section: Introductionmentioning
confidence: 99%
“…Respecto a las actividades enzimáticas PON1, existen varios estudios en la literatura que refieren una menor actividad AREasa en poblaciones ocupacionalmente expuestas a OF (Zhang et al 2014, Gokce et al 2016 con respecto a poblaciones control, lo cual coincide con los resultados obtenidos en este trabajo. En cuanto a la actividad CMPAasa, hasta donde sabemos sólo existe un estudio realizado por Bernal-Hernández et al (2014) en agricultores indígenas de México, en el que reportaron tendencias de una disminución en la actividad CMPAasa en el grupo expuesto con respecto al grupo no expuesto.…”
Section: Discussionunclassified